Difficult on Purpose: Embodied Learning in the Feldenkrais Method and Beyond. - Fredricksson, Kristin (Paragraph, 2024)
This article analyses how difficulties are used as learning tools in the Feldenkrais Method of somatic education (FM), drawing on Moshe Feldenkrais's theory and teachings, my experience as a practitioner since 2007 and my use of FM in postgraduate academic teaching. Performer training, particularly Eugenio Barba's work, offers a wider context of embodied practice. FM challenges the parameters of difficulty, framing it as inherently productive. Key difficulties used productively in FM are the non-habitual, constraints, differentiation, diffuse attention and disorientation. To demonstrate the connection between physical and intellectual difficulties, I draw on Sara Ahmed's queer phenomenological approach to orientation and Maxine Sheets-Johnstone's argument for the 'primacy of movement'. I offer new ways of thinking about difficulty as emergent rather than intrinsic, expanding outwards from clearly embodied practices towards intellectual ones. To anchor this, I refer to an experiment in Israel aiming to integrate 'organic' and 'scholastic' learning through FM.